Resultados de la evaluación de competencias profesionales a estudiantes de enfermería del Ecuador - Velasco Garcés, María de Lourdes A. (2017)
Context: in Ecuador, the national education system is in processes of change. The State, through its governing body, is implementing regulations, evaluations categorizations and processes to improve the quality of universities. The faculties, schools or nursing careers of the Country should promote the quality of training. In this context, research is presented like this: What is the result of professional nursing competencies of the senior students of the School of Nursing (Rotating internship) of the 21 faculties, schools or nursing careers of universities in the year 2014?Objective: To apply a simulation procedure of evaluation of competencies aimed at final year students of the School of Nursing, which let evaluate and facilitate student understand-ing of both the content of the reagents and the manner of presentation, taking into account the guidelines used by the Board of Evaluation, Accreditation and Quality Assurance of High-er Education.Design: the research was field with a descriptive, evaluative and transverse level. Place and individuals: the study was national in 21 Academic Units and a total of 2167 stu-dents of the last year or semester in nursing careers (Rotating Internship).Main measurements: it was applied only once in 2014 an objective evaluation question-naire through 60 reagents.Results: vocational subjects exceeding 70% achievement in learning are: Surgical clinical, reproductive health, neonates, child and adolescent, maternal child nursing, community nursing and mental health. By subjects, the overall average of correct answers from all facul-ties, schools and nursing careers of the 21 universities is 43.3%. Students achieve better learning outcomes and competences in Community Nursing, Nursing Reproductive Health, Nursing Mother and Child and lower scores on Research and Epidemiology, Fundamentals of Nursing / Basic Nursing I and II and administration.Conclusion: the global results show strengths and weaknesses of the professional skills of the students by subjects. There are differences in the results according to academic units and the contexts in which they are located.